Plastic Behavior of Beams with Mid-Depth Web Openings - Afifi Aglan, Ahmed; Qaqish, Samih (Engineering Journal, 1982)
It has become common practice to cut holes in the webs of steel beams in building structures in order to provide for the passage of service facilities such as ducts, water and sewage pipes, etc. This results in a considerable reduction in the depth between the ceiling and the floor above. Consequently, considerable savings in building costs can be achieved. The plastic analysis of steel I-beams with a single rectangular mid-depth hole has been extensively studied. Analysis was carried out by assuming the predicted normal and shear stresses at failure in the top and bottom parts of the beam, and obtaining the failure load (bending moment and shearing force at the center of the hole) by considering the equilibrium of the external and the assumed internal forces. These analyses are somewhat lengthy compared to the authors analysis. This paper presents a new approach to the problem, in which plastic hinges are assumed at the corner of the hole. Formulas for the predicted failure loads have been derived and can be solved by hand or by small calculators. Analyses of beams with double or multiple holes have also been investigated. The authors analysis can be extended to provide a simpler solution for such beams.